Identification of a Lytic-Cycle Epstein-Barr Virus Gene Product That Can Regulate PKR Activation - Poppers, Jeremy (American Society for Microbiology, 2003)
The Epstein-Barr virus (EBV) SM protein is a posttranscriptional regulator of viral gene expression. Like many transactivators encoded by herpesviruses, SM transports predominantly unspliced viral mRNA cargo from the nucleus to the cytosol, where it is subsequently translated. This activity likely involves a region of the protein that has homology to the herpes simplex virus type 1 (HSV-1) ICP27 gene product, the first member of this class of regulators to be discovered. However, SM also contains a repetitive segment rich in arginine and proline residues that is dispensable for its effects on RNA transport and splicing. This portion of SM, comprised of RXP triplet repeats, shows homology to the carboxyl-terminal domain of Us11, a double-stranded RNA (dsRNA) binding protein encoded by HSV-1 that inhibits activation of the cellular PKR kinase. To evaluate the intrinsic ability of SM to regulate PKR, we expressed and purified several SM protein derivatives and examined their activity in a variety of biochemical assays. The full-length SM protein bound dsRNA, associated physically with PKR, and prevented PKR activation. Removal of the 37-residue RXP domain significantly compromised all of these activities. Furthermore, the SM RXP domain was itself sufficient to inhibit PKR activation and interact with the kinase. Relative to its Us11 counterpart, the SM RXP segment bound dsRNA with reduced affinity and responded differently to single-stranded competitor polynucleotides. Thus, SM represents the first EBV gene product expressed during the lytic cycle that can prevent PKR activation. In addition, the RXP repeat segment appears to be a conserved herpesvirus motif capable of associating with dsRNA and modulating activation of the PKR kinase, a molecule important for the control of translation and the cellular antiviral response.